Mobility, balance and muscle performance according to self-efficacy for falls in the elderly - Carolina Raíssa Bento Pereira da Silva; Ricardo Oliveira Guerra; Aline Medeiros Cavalcanti da Fonsêca; Andréa de Carvalho Gomes; Álvaro Campos Cavalcanti Maciel
Introduction Changes in mobility, postural balance and muscle strength in the aging process may cause a fall in the elderly by changing or not perceived self-efficacy in preventing falls, the goal is to compare mobility, body balance and muscle performance according to self-efficacy for falls in community-dwelling elderly women. Materials and methods A comparative study of cross-section, with 63 community-dwelling elderly. We evaluated sociodemographic data, cognition (Mini-Mental State Examination), efficacy for falls (International Efficacy Scale for Falls, Brazil), mobility (Timed Up and Go Test), body balance by Berg Balance Scale, Balance Master System: Modified Clinical Test of Sensory Interaction on Balance (mCTSIB), Tandem walk (TW) Sit to Stand (STS) and muscular performance by isokinetic dynamometry. Using the cutoff point at or above 23 points, two groups, G1 with low perceived efficacy in preventing falls (n = 36) and G2 with high perceived efficacy in preventing falls (n = 27) were allocated. Student's t test was performed for comparison between groups, with p value of 0.05. Results Comparing the elderly women regarding the efficacy of falls, significant differences were observed in the variables Timed Up and Go Test (p = 0.04), speed of oscillation test mCTSIB (p = 0.01) and the isokinetic dynamometry knee extension movement, peak torque (p = 0.04) and power (p = 0.03). Conclusion Comparing community-dwelling elderly women with low and high efficacy for falls, significant differences were in variables related to mobility, body balance and muscle function.